Exploring the Crosstalk Between LMNA and Splicing Machinery Gene Mutations in Dilated Cardiomyopathy - Zahr, Hind C.; Jaalouk, Diana E. (Frontiers in Genetics, 2018)
Mutations in the LMNA gene, which encodes for the nuclear lamina proteins lamins A and C, are responsible for a diverse group of diseases known as laminopathies. One type of laminopathy is Dilated Cardiomyopathy (DCM), a heart muscle disease characterized by dilation of the left ventricle and impaired systolic function, often leading to heart failure and sudden cardiac death. LMNA is the second most commonly mutated gene in DCM. In addition to LMNA, mutations in more than 60 genes have been associated with DCM. The DCM-associated genes encode a variety of proteins including transcription factors, cytoskeletal, Ca2+-regulating, ion-channel, desmosomal, sarcomeric, and nuclear-membrane proteins. Another important category among DCM-causing genes emerged upon the identification of DCM-causing mutations in RNA binding motif protein 20 (RBM20), an alternative splicing factor that is chiefly expressed in the heart. In addition to RBM20, several essential splicing factors were validated, by employing mouse knock out models, to be embryonically lethal due to aberrant cardiogenesis. Furthermore, heart-specific deletion of some of these splicing factors was found to result in aberrant splicing of their targets and DCM development. In addition to splicing alterations, advances in next generation sequencing highlighted the association between splice-site mutations in several genes and DCM. This review summarizes LMNA mutations and splicing alterations in DCM and discusses how the interaction between LMNA and splicing regulators could possibly explain DCM disease mechanisms.